Contribution of polymorphisms in the LEP, LEPR and RETN genes on serum leptin and resistin levels in young adults from Mexico - López-Quintero, A.; García-Zapién, A. G.; Flores-Martínez, S. E.; Díaz-Burke, Y.; González-Sandoval, C. E.; Lopez-Roa, R. I.; Medina-Díaz, E.; Muñoz-Almaguer, M. L.; Sánchez-Corona, J. (Cellular and Molecular Biology, 2017)
Polymorphisms in the LEP (G–2548A and A19G), LEPR (A326G, A668G and G3057A) and RETN (C–420G and G+62A) genes were documented according to their association with alterations in biochemical parameters such as glucose, insulin and lipid profiles, along with serum leptin and resistin concentrations. The aim of the study was to establish any contribution of the G-2548A and A19G polymorphisms of the LEP gene, the A326G, A668G and G3057A polymorphisms of the LEPR gene, and the C-420G and G+62A polymorphisms of the RETN gene to serum leptin and resistin levels in Mexican young adults. Clinical and biochemical variables, serum leptin and resistin levels, and genotype profiles were analysed in 66 Mexican young adults. Seven polymorphisms in the LEP, LEPR and RETN genes were genotyped using polymerase chain reaction–restriction fragment length polymorphisms analysis. Individuals carrying allele 3057A of the G3057A polymorphism in the LEPR gene showed significantly higher leptin concentrations than those bearing the genotype G/G (43.78 ± 39.11 vs 28.20 ± 14.12 ng/mL; p = 0.021). There were no associations of serum leptin or resistin levels according to the genotype of the other six analysed polymorphisms. Our results suggest that the allele 3057A of the LEPR G3057A polymorphism contributes to increased serum leptin levels in Mexican young adults.